Objective Structured Practical Examinations as a Formative Assessment Tool in Community Medicine - Arya, Dr. Vimal; Chouksey, Dr. Mahendra; Mathur, Dr. B. P. (International Journal of Innovative Research in Medical Science, 2018)
Background - Assessment for practical skills in medical education has lot of scope for improvement. Objective Structured Practical Examination (OSPE) has been considered as one such method. Feedback is given to the students and teachers after the examination. Methods - Five stations were designed based on the practical examination on housing conditions. A feedback questionnaire was designed for the students and the faculty about their overall experience about OSPE, its feasibility and objectivity. Results - Majority of the students (90%) found OSPE as a better method of assessment as compared to traditional practical method, 92% said OSPE prepares them better, 95% found OSPE is a better stimulus for study, 98% found it more reliable. Conclusion -The faculty was happy with the feedback part associated with OSPE. But preparing a checklist was a time-consuming task. We conclude that OSPE is useful in community medicine for formative assessment as it gives feedback to the students and teachersand provides integration in teaching and learning.